Efficient recovery of vanadium using lysine. (October 2022) - Peng, Hao; Tang, Dan; Liao, Miao; Wu, Bo; Wu, Yuting; Fan, Xiaoyi; Lin, Yinhe
Abstract: This study presents an environmental-friendly technique for vanadium precipitation using lysine. Experimental results indicate that 99.4 % of the vanadium is precipitated under the select reaction conditions within the lysine. During the precipitation process, the vanadium exists as negatively charged polyoxometalates, while the lysine is positively charged. The negative vanadium polyoxometalates precipitate out through electrostatic interactions. The results shown in this study introduce a new way to utilize lysine and a new treatment for polyoxometalates. Graphical abstract: Unlabelled Image Highlights: Vanadium was efficiently recovered. Lysine was a great precipitant for vanadium recovery. Lysine can promote dehydration condensation reactions of polyoxometalates.